Penamaan Tempat Usaha di Umakatahan : Kajian Semantik - Fenesiana Claudina Eunike Tabun; Ramires Mario Lurdes Bria; Maria Elishabet Bria; Emeliana Tai (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The purpose of this research is to analyze the naming of business places in Umakatahan. The theory used in analyzing naming is Chaer’s theory (2009). This study uses a qualitative research model. The data collection process carried out in this study used the documentation method, followed by the observing and nothing method. The data in this study are presented in a descriptive form or informal method. Based on the result of this study it was found that from 5 data on the naming of bussines places in Umakatahan, there were grammaticalmeanings. In addition, the naming process that occurs in 5 data on the naming of business premises in Umakatahan, produces 5 data based on inventors or makers, data based on new names, data based on place of origin, data based on uniqueness and new naming. So, it can be concluded that the naming of business places in Umakatahan is dominated by the process of the inventor or maker because most of the business places use the name of the owner or maker.